Dictionaries on AC^0 RAMs: Query Time Theta(√log n/log log n) is Necessary and Sufficient - Andersson, Arne; Miltersen, Peter Bro; Riis, Søren; Thorup, Mikkel (BRICS Report Series, 1997)
[No abstract available for preview]